Upaya Guru BK dalam Mengentaskan Permasalahan Siswa yang Mengalami Self Efficacy Rendah - Putri Sakinah Lubis; Alizamar Alizamar; Syahniar Syahniar (Universitas Negeri Padang, 2019)
Ideally in following the learning process students need to have a strong self efficacy, because with self-efficacy, students will try harder in doing academic tasks and manage their own learning. In fact there are still field students who experience low self efficacy. This study aims to describe the efforts of BK teachers in alleviating the problems of students who have low self efficacy. This study uses a quantitative-descriptive approach. The subjects of the study were Guidance and Counseling teachers of SMP Negeri Kota Padang with 39 people. The instrument used is Likert Scale. Data were analyzed using percentage technique. The results revealed that the efforts of BK teachers in: (1) Identify the problem of low self efficacy is in good enough category. (2) Analyzing the cause of low self efficacy is in good enough category. (3) Identifying parties that help to eradicate low self efficacy are in good category. (4) Developing a low self-efficacy service plan is in good enough category. (5) Implementing low self-efficacy services is quite good (6) and Evaluating low self-efficacy services are in fairly good category.